2004
DOI: 10.1021/ja046825g
|View full text |Cite
|
Sign up to set email alerts
|

Stoichiometric and Catalytic H/D Incorporation by Cationic Iridium Complexes:  A Common Monohydrido-Iridium Intermediate

Abstract: A mechanistic study of the stoichiometric and catalytic H/D exchange reactions involving cationic iridium complexes is presented. Strong evidence suggests that both stoichiometric and catalytic reactions proceed via a monohydrido-iridium species. Stoichiometric deuterium incorporation reactions introduce multiple deuterium atoms into the organic products when aryliridium compounds CpPMe(3)Ir(C(6)H(4)X)(OTf) (X = H, o-CH(3), m-CH(3), p-CH(3)) react with D(2). Multiple deuteration occurs at the unhindered positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 143 publications
(79 citation statements)
references
References 66 publications
2
75
1
1
Order By: Relevance
“…13,14 We found that 1 exchanges tritium most easily with the protons of aromatic rings. Exchange was also observed in simple alkyl groups that are activated by electron-withdrawing heteroatoms, such as nitrogen or oxygen, though to a lesser degree.…”
Section: Introductionmentioning
confidence: 87%
“…13,14 We found that 1 exchanges tritium most easily with the protons of aromatic rings. Exchange was also observed in simple alkyl groups that are activated by electron-withdrawing heteroatoms, such as nitrogen or oxygen, though to a lesser degree.…”
Section: Introductionmentioning
confidence: 87%
“…[59] Mit den N-heterocyclischen Iridium-Carben-Komplexen 77 (X = Cl, I) und 78 (R = H, Cl) und [D 4 ]Methanol beobachteten Peris et al ebenfalls einen effizienten H/D-Austausch unter anderem bei Diethylether, Ethylmethylketon, Isopropanol und Styrol. [60] Die stetige Weiterentwicklung homogener Iridiumkatalysatoren zur C-H-Aktivierung [61] dürfte in Zukunft immer mehr gut deuterierbare Verbindungen zugänglich machen.…”
Section: Iridium-katalysierter H/d-austauschunclassified
“…[183] The ability of these complexes to undergo reversible metalation/solvolysis of the substituents on the NHC seem to make them very active in deuteration reactions. [184] Interesting selectivities were obtained (Scheme 23), and these complexes certainly deserve more investigation. The same group recently reported a chiral analogue of 105 and tested it in the chiral diboration of olefins.…”
Section: H/d Exchange (Ir)mentioning
confidence: 99%